Phytobiotic effect of Psidium guajava leaf powder on productivity and quality of the egg of laying hens - Martínez, Y.; Rodríguez, R.; Pupo, G. E.; Rosabal, O.; Colmo, C.; Valdivié, M. (Cuban Journal of Agricultural Science, 2020)
In order to evaluate the phytobiotic effect of Psidium guajava (guava) leaf powder on the productivity and quality of the egg of laying hens, a phytochemical screening of the leaves under study was previously developed. A total of 160 White Leghorn L-33 hens, of 27 weeks old, were randomly distributed for 70 days in four treatments, with 10 repetitions each, and four hens per repetition. The treatments consisted on a control diet (T0) and the addition of 0.5 (T1), 1.0 (T2) and 1.5 % (T3) of Psidium guajava leaf powder. Saponins, reducing sugars, quinones, triterpenes, free amino acids, anthocyanidins, tannins and flavonoids (++) were detected in P. guajava leaves. The addition with 0.5 % of P. guajava leaf powder improved (P <0.05) the mass conversion (2.41 kg/kg), the production (83.46 %) and the egg weight (54.75 g) compared to the control, without notable changes (P> 0.05) for the food intake and the unfit eggs. In addition, this treatment (0.5 %) increased the shell thickness (0.26 mm) and the yolk color (7). However, the addition of 1.5 of P. guajava decreased (P <0.05) the height of the white (5.97 mm) with respect to T0. The shell surface and yolk height did not change as a result of the experimental treatments (P> 0.05). The addition of 0.5 % of P. guajava leaf powder to laying hen diets is recommended to improve productivity and some indicators of egg quality. Key words: additive, laying hen (ave de postura), guava, biological response